Associação de polimorfismo do gene PIT1 com características de produção de carne em bovinos da raça Canchim - Carrijo, Sônia Mara (2004)
The PIT1 gene codes for the pituitary transcription factor Pit-1, which is critical for the activation of the expression of prolactin and growth hormone genes, in addition to participating in the activation of PIT1 itself. The objective of the present study was to investigate the effect of HinfI polymorphism of this gene on meat production traits. The sample consisted of 509 Canchim animals born between 1998 and 2000. The sample included a traditional line (GG1) consisting of 5/8 Charolais genome breed and 3/8 of the Zebu breeds, Nelore, Guzerá and Indubrasil, and a new line (GG2) with 21/32 Charolais genome and 11/32 of the Nelore breed. The genotypes for the PIT1 gene were identified by PCR-RFLP. Genotype effect on phenotypic values for birth weight (BW), standardized weaning weight (W240) and at 12 month of age weight (W365), and on average daily weight gain to the born at weaning (GMND) and to the weaning at 12 month of age (GMD12), were analyzed by the least squares method. The results revealed significant effects of the interaction between genetic animal group and PIT1 genotype on W240, GMND and GMD12 (P < 0.05). The differences in mean least squares between genotype ( / ) and genotypes (+/+) and (+/ ) for W240 and GMND were significant in GG2 (P < 0,01 and p < 0,05, respectively), revealing superiority of the ( / ) genotype on that characters. The means for genotypes (+/+) and (+/ ), respectively at the W240 and GMND, did not differ from one another, suggesting a dominance effect of the HinfI (+) allele. The means effects of the HinfI ( ) allele indicated a positive effect of this allele on W240 and GMND, and the deviation estimates attributed to dominance showed a favorable effect of the HinfI ( ) allele on W240 and GMND of GG2 animals, when present in homozygosis in the genotypes of the individuals. The means of the genotypes in GG1 did not differ from one another. The difference in PIT1 behavior observed in the two genetic groups, however, may suggest the action of a quantitative trait locus linked to PIT1 segregating only in GG2 of the population studied, and not a direct effect of PIT1.